Genetic algorithms in search, optimization, and machine learning - Goldberg, David E. (David Edward) 1953- (Addison-Wesley Longman, Inc., 1989)
This book brings together - in an informal and tutorial fashion - the computer techniques, mathematical tools, and research results that will enable both students and practitioners to apply genetic algorithms to problems in many fields. Major concepts are illustrated with running examples, and major algorithms are illustrated by Pascal computer programs.